Smac mimetics and type II interferon synergistically induce necroptosis in various cancer cell lines. (1st December 2017) - Cekay, Michael John; Roesler, Stefanie; Frank, Tanja; Knuth, Anne-Kathrin; Eckhardt, Ines; Fulda, Simone
Abstract: Since cancer cells often evade apoptosis, induction of necroptosis as another mode of programmed cell death is considered a promising therapeutic alternative. Here, we identify a novel synergistic interaction of Smac mimetics that antagonize x-linked Inhibitor of Apoptosis (XIAP), cellular Inhibitor of Apoptosis (cIAP) 1 and 2 with interferon (IFN)γ to induce necroptosis in apoptosis-resistant cancer cells in which caspase activation is blocked. This synergism is confirmed by calculation of combination indices (CIs) and found in both solid and hematological cancer cell lines as well as for different Smac mimetics (i.e. BV6, Birinapant), pointing to a broader relevance. Importantly, individual genetic knockdown of key components of necroptosis signaling, i.e. receptor-interacting protein (RIP) 1, RIP3 or mixed lineage kinase domain-like pseudokinase (MLKL), significantly protects from BV6/IFNγ-induced cell death. Similarly, pharmacological inhibitors of RIP1 (necrostatin-1(Nec-1)), RIP3 (GSK′872) or MLKL (necrosulfonamide (NSA)) significantly reduce BV6/IFNγ-stimulated cell death. Of note, IFN-regulatory factor (IRF)1 is required for BV6/IFNγ-mediated necroptosis, as IRF1 silencing provides protection from cell death. By comparison, antibodies blocking tumor necrosis factor (TNF)α, TNF-related apoptosis-inducing ligand (TRAIL) or CD95 ligand fail to inhibit BV6/IFNγ-induced cell death, pointing to a mechanism independently of death receptor ligands. This is the first report showing that Smac mimetics synergize with IFNγ to trigger necroptosis in apoptosis-resistant cancer cells with important implications for Smac mimetic-based strategies for the treatment of cancer. Graphical abstract: Highlights: BV6 and IFNγ synergize to trigger necroptosis in cancer cells. RIP1, RIP3 and MLKL are required for BV6/IFNγ-induced necroptosis. IRF1 contributes to BV6/IFNγ-induced necroptosis.